2018
DOI: 10.3390/rs10050791
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Landsat-8 and Sentinel-2 Data to Support Monitoring of Dryland Ecosystems

Abstract: Drylands are the habitat and source of livelihood for about two fifths of the world's population and are highly susceptible to climate and anthropogenic change. To understand the vulnerability of drylands to changing environmental conditions, land managers need to effectively monitor rates of past change and remote sensing offers a cost-effective means to assess and manage these vast landscapes. Here, we present a novel approach to accurately monitor land-surface phenology in drylands of the Western United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 38 publications
(52 reference statements)
1
36
0
Order By: Relevance
“…For example, estimated mean start of season, maximum, and end of season NDVI values show good agreement with eMODIS-derived data, with Pearson's correlation, and mean absolute errors (MAEs) ranging from 0.72 to 0.98 and from 0.02 to 0.08, respectively. Estimated timings followed similar patterns, with HLS-derived metrics generally indicating earlier start of season, maximum, and end of season timings as compared to eMODIS which is generally consistent with previous interpretations [32]. For comparison, Zhou et al [44] used a weighted least-squares approach for temporal smoothing of HLS data and a delayed moving average technique to estimate the start of season date in grasslands along the eastern border of North Dakota and western Minnesota, with much higher data densities as compared to this study, and found fair agreement with MODIS-derived date estimates (RMSE = 11.6 days).…”
Section: Time-series Modeling and Metricssupporting
confidence: 87%
See 2 more Smart Citations
“…For example, estimated mean start of season, maximum, and end of season NDVI values show good agreement with eMODIS-derived data, with Pearson's correlation, and mean absolute errors (MAEs) ranging from 0.72 to 0.98 and from 0.02 to 0.08, respectively. Estimated timings followed similar patterns, with HLS-derived metrics generally indicating earlier start of season, maximum, and end of season timings as compared to eMODIS which is generally consistent with previous interpretations [32]. For comparison, Zhou et al [44] used a weighted least-squares approach for temporal smoothing of HLS data and a delayed moving average technique to estimate the start of season date in grasslands along the eastern border of North Dakota and western Minnesota, with much higher data densities as compared to this study, and found fair agreement with MODIS-derived date estimates (RMSE = 11.6 days).…”
Section: Time-series Modeling and Metricssupporting
confidence: 87%
“…We used a regression tree modeling framework (similar to [32]) for the spatial estimation of weekly NDVI values derived from HLS data acquired from 2016 to 2018. This framework relies on: (1) the generation of spatial inputs (e.g., weekly HLS composites, week of year, and year raster data) to serve as covariates within regression tree models; (2) extraction of model tuning, training, and testing data from raw NDVI image composites; (3) hyperparameter optimization (i.e., number of rules and committees); and (4) application of calibrated and validated models to predict NDVI at each pixel and time step (e.g., weekly), as described in more detail below.…”
Section: Automated Time-series Modeling and Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…The green up, or start of season (SOS), dates estimated from the VIIRS-HLS fused data had a closer agreement, i.e., mean absolute deviation (MAD), of 8 days with the in situ USA-NPN dates than with HLS (MAD of 14 days). Pastick et al (2018) [62] also pointed out that NDVI, SWIR, blue, green and NIR bands in Sentinel-2 and Landsat-8 are highly consistent (R 2 > 0.90) in HLS data. A review of the literature on forest mapping reveals that such studies focused on the use of multi-temporal images representing different periods within the growing season to map broad forest types and their seasonality, rather than focusing on specific phenological stages [63][64][65][66][67].…”
Section: Integration Of Sentinel-2 Data With Other Imagerymentioning
confidence: 87%
“…The fire detection map derived from Landsat-8 was influenced by an artificial effect related to problems with HLS cloud masking [42]. The Landsat-8 cloud detection algorithm (HLS version 1.3) sometimes confused bright targets with clouds, then dilated the target in the Landsat-8 cloud mask, resulting in anomalous square-shaped patterns of change in the Landsat-8 data.…”
Section: Discussionmentioning
confidence: 99%